24-Track Narrative? Robert Altman’s Nashville - Altman, Rick (Cinémas)

(untitled) (Cinémas, 1991)
An analysis of the sound track of Robert Altman's Nashville shows that the filmmaker goes beyond the conventions of traditional sound recording in his use of the twenty-four tracks for twenty-four separate characters. As a result the film initially appears innovative since a traditional technology is transformed into a new one with the result that the simple linear approach opens up into three dimensions. But this non-hierarchic openness oriented to spectator choice yields in the end to the narrative logic of the traditional linear model.